Mutu Organoleptik dan Mutu Kimia Mie Kering dengan Variasi Penambahan Tepung Daun Brokoli sebagai Pangan Fungsional - Wildatul Khairi; Alfira Alfira; Oslida Martony (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Noodles are commonly made from wheat flour, which is high in carbohydrates but low in fiber, vitamins, and minerals. To enhance their nutritional value, this study used broccoli leaf flour, a vegetable source rich in nutrients and antioxidants. The aim was to evaluate the organoleptic and chemical qualities of dried noodles with added broccoli leaf flour. The study used a completely randomized design with three treatments and two replications. Organoleptic tests (color, aroma, texture, and taste) were conducted by 60 panelists. Chemical analysis measured carbohydrate, protein, fat, calcium, fiber, and moisture content. The results showed that noodles with 10 grams of broccoli leaf flour (treatment B) were most preferred by panelists. This treatment also had improved nutritional content, especially in fiber and calcium, while maintaining acceptable product quality. In conclusion, broccoli leaf flour is a promising ingredient to improve the nutritional value of dried noodles and develop functional food that is well-accepted by consumers.